Alit-belite-calcium sulphoaluminate cement clinker prepared from high-silicon low-grade limestone and aluminum solid waste and method

The preparation of Alite-Belite-Calcium sulfaluminate cement clinker by compiling high-silicon low-grade limestone and aluminum solid waste is solved, and the problem of low utilization rate of high-silicon low-grade limestone and aluminum ash in the existing technology is achieved. The reduction of cement production costs and the resource utilization of solid waste have promoted the low-carbon development of the cement industry, while maintaining the excellent mechanical properties of cement.

CN119118544APending Publication Date: 2024-12-13NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411313735.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The utilization rates of high-silicon low-grade limestone and aluminum ash in the prior art are low, resulting in high cement production costs and environmental pollution problems, and it is difficult to effectively utilize high-silicon low-grade limestone resources.

Method used

Alite-Belite-Calcium Sulfur-Aluminate cement clinker is prepared by high silicon low-grade limestone and aluminum solid waste. It is prepared by grinding and mixing, and calcining is added, metal ionic oxides and mineralizers are added to reduce the firing temperature. and CO2 emissions to improve the early strength and middle and late strength of cement clinker.

Benefits of technology

It has achieved high substitution rate of high silicon low grade limestone and complete substitution of aluminum solid waste, which has reduced cement production costs, improved solid waste utilization rate, promoted the low-carbon development of the cement industry, and maintained high and early strength of cement. , low alkalinity, corrosion resistance and micro-expansion properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118544A_ABST
    Figure CN119118544A_ABST
Patent Text Reader

Abstract

The invention discloses alite-belite-calcium sulphoaluminate cement clinker prepared from high-silicon low-grade limestone and aluminum solid waste and a method, and the mineral phase of the clinker comprises the following components in percentage by mass: 30-50% of C3S, 30-50% of C2S, 10-30% of C4A3, 0-5% of C4AF, 0-5% of CaSO4 and metal ion oxide. 20-50% of high-silicon low-grade limestone is used for partially replacing a calcium raw material and completely replacing a siliceous raw material; the aluminum solid waste completely replaces an aluminum raw material and an iron raw material. The alite-belite-calcium sulphoaluminate cement clinker prepared by the method is high in utilization rate of the low-grade limestone and the aluminum solid waste, does not need to improve a traditional Portland cement clinker production process, and is good in burnability, low in sintering temperature, high in hardening speed, high in early strength and stable in later strength development compared with the latter. The problem of utilization of low-grade limestone and aluminum solid waste is effectively solved, the cement clinker production cost is reduced, and carbon emission in the cement production process is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cement material production, and specifically relates to an alite-belite-calcium sulfoaluminate cement clinker prepared from high-silicon low-grade limestone and aluminum solid waste and a method. Background Art

[0002] Most of the limestone in my country is medium-low grade limestone. Low-grade limestone in different regions has different characteristics. The common point is that it has low calcium content and high silicon content, which leads to poor grindability. High magnesium content will not only cause the problem of low strength due to less calcium silicate minerals in the clinker, but also bring about the problem of poor volume stability caused by excessive free magnesium oxide. In addition, low-grade limestone may also contain high-sulfur minerals, which will bring difficulties to sintering clinker. Therefore, the effective use of high-silicon low-grade limestone resources is of practical significance to cement production, which can save resources, reduce costs, and reduce negative impacts on the environment.

[0003] Aluminum ash is a solid waste generated during the production, consumption and reuse of aluminum. With the continuous increase in aluminum production, the output of aluminum ash is also increasing. At present, the utilization of aluminum ash is basically to recycle metallic aluminum. The harmless treatment of its byproducts requires high process equipment and high costs. Most of the recycled secondary aluminum ash is directly stored or landfilled, which not only occupies land resources, but also harms the environment. Using aluminum ash as an aluminum raw material directly to prepare high-aluminum cement clinker system can not only solve the problem of low aluminum ash utilization and high recycling cost, but also alleviate the problem of shortage of high-quality bauxite resources, and further reduce the cost of cement production.

[0004] Alite-belite-calcium sulfoaluminate cement clinker is a new cement clinker system. From the perspective of mineral composition, it can be considered that a small amount of calcium sulfoaluminate is introduced into silicate cement based on alite as the main mineral phase, which reduces the energy consumption of cement production, as well as the calcium demand and CO2 emissions. Alite-belite-calcium sulfoaluminate cement has the excellent characteristics of high early strength, low alkalinity, corrosion resistance, and micro-expansion, and the strength in the middle and late stages continues to develop without shrinkage. Based on the low calcium demand of alite-belite-calcium sulfoaluminate cement, it can greatly promote the utilization of high-silicon low-grade limestone. At the same time, due to the introduction of calcium sulfoaluminate phase, cement production needs to be mixed with aluminum raw materials. The use of aluminum solid waste to replace high-cost bauxite resources to reduce the production of alite-belite-calcium sulfoaluminate cement has very important economic value and practical production significance. Summary of the invention

[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide an alite-belite-calcium sulfoaluminate cement clinker prepared by compounding high-silicon low-grade limestone and aluminum solid waste in view of the shortcomings of the prior art, so as to solve the technical problem of low utilization rate of high-silicon low-grade limestone and aluminum ash in the prior art.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The invention discloses an alite-belite-calcium sulfoaluminate cement clinker prepared from high-silicon low-grade limestone and aluminum solid waste. The mineral phase composition in the clinker, measured by mass percentage, includes C3S: 30-50%, C2S: 30-50%, C4A3$: 10-30%, C4AF: 0-5%, CaSO4: 0-5%, and metal ion oxides.

[0007] Furthermore, the oxide contents in the clinker include, by mass percentage, CaO: 50-65%, SiO2: 15-25%, Al2O3: 8-15%, Fe2O3: 0-3%, and SO3: 3-8%; the raw materials of the alite-belite-calcium sulfoaluminate cement clinker include high-silicon low-grade limestone, aluminum solid waste, gypsum and mineralizer.

[0008] Furthermore, the metal ion oxide includes at least one of MnO2, ZnO, and CuO, and further includes Fe2O3, K2O, Na2O, etc.; and the mineralizer is CaF2.

[0009] Specifically, the high-silicon low-grade limestone in the present invention has a CaO content of 39-46 wt %, and a SiO2 content of 18-29 wt %.

[0010] Specifically, the aluminum solid waste in the present invention is aluminum ash or fly ash, or a mixture of the two in any proportion; the Al2O3 content in the aluminum solid waste is greater than 60 wt%.

[0011] Specifically, by mass percentage, the calcium raw material content in the raw meal of the present invention is 70-83%, the aluminum raw material content is 5-15%, and the sulfur raw material content is 5-10%.

[0012] Preferably, the mineralizer described in the present invention is CaF2.

[0013] Furthermore, the present invention also provides a method for preparing the above alite-belite-calcium sulfoaluminate cement clinker, comprising the following steps: (1) Grinding calcium, aluminum and sulfur-containing raw materials and mixing them thoroughly, then adding metal ion oxides and mineralizers to mix them evenly to obtain raw meal, adding deionized water to the raw meal and mixing them evenly, and pressing and molding them to obtain raw meal cakes; (2) calcining the raw material cake of step (1) at 1250°C-1350°C for 15-30 minutes, then taking it out and rapidly cooling it to obtain the raw material cake.

[0014] Specifically, in step (1), the metal ion oxide is added at 0.5-2% of the mass of cement clinker; and the mineralizer is added at 1-2% of the mass of cement clinker.

[0015] Furthermore, the metal ion oxide is preferably ZnO, which is added using ZnSO4·H2O as a raw material; the K2O is added using K2CO3 as a raw material; and the Na2O is added using Na2CO3 as a raw material.

[0016] Specifically, in step (1), the calcium raw materials are ordinary limestone and low-grade limestone, the CaO content of ordinary limestone is ≥48 wt%, and the CaO content of low-grade limestone is 39-46 wt%; the aluminum solid waste is aluminum ash or fly ash, or a mixture of the two in any proportion, with an Al2O3 content of ≥60 wt%; the SO3 content of the sulfur-containing raw material is ≥40 wt%; and in terms of mass percentage, the calcium raw material content in the raw meal is 70-83%, the aluminum raw material content is 5-15%, and the sulfur raw material content is 5-10%.

[0017] Specifically, in step (1), all raw materials are ground and thoroughly mixed, and the mixed powder particle size is 74 µm mesh sieve residue ≤ 5 wt%.

[0018] Specifically, in step (2), the heating rate of calcination is 5-10°C / min, and after calcination, the mixture is rapidly cooled to room temperature by air cooling.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses a high-replacement amount of high-silicon low-grade limestone and aluminum solid waste to prepare alite-belite-calcium sulfoaluminate cement clinker. The low calcium demand characteristic of alite-belite-calcium sulfoaluminate cement clinker promotes high-silicon low-grade limestone (CaO≤48%) to replace high-grade limestone (CaO>48%) as a calcium replacement raw material, and the replacement rate is high. When the CaO content of high-silicon low-grade limestone is 35-46%, its replacement rate can reach 35-50%; at the same time, due to the high aluminum content (Al2O3 content>60%) in aluminum solid waste such as aluminum ash, aluminum solid waste can be used to completely replace bauxite as aluminum raw material.

[0020] (2) The present invention uses trace impurity ions in high-silicon low-grade limestone and aluminum solid waste to play a certain role in fluxing and mineralization. The sintering temperature of alite-belite-calcium sulfoaluminate cement clinker is low and it is prepared by calcining at a temperature of 1250-1350°C. The trace amounts of MgO and metal ions such as Zn, Mn, Cu, K, and Na contained in high-silicon low-grade limestone and aluminum solid waste can further reduce the sintering temperature, reduce sintering coal consumption and CO2 emissions. At the same time, it can promote the coexistence of alite and calcium sulfoaluminate in the temperature range of 1250-1350°C to a certain extent, thereby promoting the sintering of alite-belite-calcium sulfoaluminate cement.

[0021] (3) Due to the use of inferior raw materials, the mechanical properties of cement are usually greatly reduced. However, the early and late mechanical properties of the alite-belite-calcium sulfoaluminate cement prepared by the present invention using high-silicon low-grade limestone and aluminum solid waste as substitutes are relatively small, and still have the performance characteristics of high early strength, and continuous development of strength in the middle and late stages without shrinkage. At the same time, due to the presence of the calcium sulfoaluminate ore phase, the alite-belite-calcium sulfoaluminate cement also has the excellent characteristics of low alkalinity, corrosion resistance, and micro-expansion, and has a wider range of applications, and can be used for repair materials, prefabricated components, anti-corrosion engineering, etc.

[0022] (4) The present invention uses high-silicon low-grade limestone and aluminum solid waste with a high substitution rate to prepare cement clinker, which saves raw materials for cement production and promotes the resource utilization of solid waste, reduces cement production costs, improves the comprehensive utilization rate of low-grade limestone and aluminum solid waste, and also promotes the development of cement towards a low-carbon direction. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0024] Figure 1 The XRD diagram of the alite-belite-calcium sulfoaluminate cement clinker minerals of Examples 1 to 5.

[0025] Figure 2 The compressive strength bar graphs of the cement of Examples 1 to 5 after hydration for 3 days, 7 days and 28 days. DETAILED DESCRIPTION

[0026] The present invention can be better understood with reference to the following examples.

[0027] The present invention uses limestone, two kinds of high-silicon limestone with different silicon contents, sandstone, fly ash, aluminum ash, gypsum, bauxite and the like as raw materials, and their chemical compositions are shown in Table 1.

[0028] Table 1 Chemical composition of raw materials (wt / %)

[0029] The raw material proportions in Examples 1-5 are shown in Table 2.

[0030] Table 2 Raw material ratio (wt / %)

[0031] a. Replacement rate refers to the amount of limestone replaced Example 1

[0032] The preparation method of alite-belite-calcium sulfoaluminate cement in Example 1 is as follows: Grind each raw material with a planetary mill to a fineness of 74μm square hole sieve with a sieve residue of <5%. Weigh the weight percentages as follows: 75.14% limestone, 10.38% sandstone, 7.54% bauxite, 9.70% gypsum; the ions added according to the oxide content in the clinker are ZnO: 1.0%, CaF2: 1.0%. Mix the weighed raw materials for 12 hours to prepare raw material powder; add 8% water by weight to the raw material powder, mix evenly, press it into a 60mm*60mm*5mm square raw material cake with a press, and dry it in a 100℃ blast dryer for 8 hours. After drying, heat the raw material cake to 900℃ at a heating rate of 10℃ / min and keep it warm for 30 minutes, then heat it to 1300℃ and keep it warm for 30 minutes. Then quickly take it out and air cool it to room temperature to obtain alite-belite-calcium sulfoaluminate clinker. The product XRD diagram is as follows Figure 1 The quantitative results of clinker minerals are shown in Table 3. The clinker is mixed with 8% by mass of dihydrate gypsum to obtain a mixed powder, which is ground by a disc vibration mill to a particle size of about 74 μm and a sieve residue of ≤5%, to obtain alite-belite-calcium sulfoaluminate cement. Example 2

[0033] The preparation method of alite-belite-calcium sulphoaluminate cement in Example 2 is as follows: Grind the raw materials with a planetary mill to a fineness of 74μm square hole sieve with a sieve residue of <5%. Weigh the weight percentages as follows: 68.41% limestone, 9.34% high silicon limestone 2, 13.28% sandstone, 8.52% aluminum ash, 9.97% gypsum; the ions added according to the oxide content in the clinker are ZnO: 1.0%, CaF2: 1.0%. Mix the weighed raw materials for 12 hours to prepare raw material powder; add 8% water by weight to the raw material powder, mix evenly, press it into a 60mm*60mm*5mm square raw material cake with a press, and dry it in a 100℃ blast dryer for 8 hours. After drying, heat the raw material cake to 900℃ at a heating rate of 10℃ / min and keep it for 30 minutes, then heat it to 1300℃ and keep it for 30 minutes. Then it is quickly taken out and air-cooled to room temperature to obtain alite-belite-calcium sulphoaluminate clinker. The product XRD pattern is as follows: Figure 1 The quantitative results of clinker minerals are shown in Table 3. The clinker is mixed with 8% by mass of dihydrate gypsum to obtain a mixed powder, which is ground by a disc vibration mill to a particle size of about 74 μm and a sieve residue of ≤5%, to obtain alite-belite-calcium sulfoaluminate cement. Example 3

[0034] The preparation method of alite-belite-calcium sulfoaluminate cement in Example 3 is as follows: Grind the raw materials with a planetary mill to a fineness of 74μm square hole sieve with a sieve residue of <5%. Weigh the weight percentages as follows: 53.15% limestone, 25.99% high silicon limestone 2, 5.91% aluminum ash, 5.32% fly ash, 9.64% gypsum; the ions added according to the oxide content in the clinker are ZnO: 1.0%, CaF2: 1.0%. Mix the weighed raw materials for 12 hours to prepare raw material powder; add 8% water by weight to the raw material powder, mix evenly, press it into a 60mm*60mm*5mm square raw material cake with a press, and dry it in a 100℃ blast dryer for 8 hours. After drying, heat the raw material cake to 900℃ at a heating rate of 10℃ / min and keep it for 30 minutes, then heat it to 1300℃ and keep it for 30 minutes. Then it is quickly taken out and air-cooled to room temperature to obtain alite-belite-calcium sulphoaluminate clinker. The product XRD pattern is as follows: Figure 1 The quantitative results of clinker minerals are shown in Table 3. The clinker is mixed with 8% by mass of dihydrate gypsum to obtain a mixed powder, which is ground by a disc vibration mill to a particle size of about 74 μm and a sieve residue of ≤5%, to obtain alite-belite-calcium sulfoaluminate cement. Example 4

[0035] The preparation method of alite-belite-calcium sulphoaluminate cement in Example 4 is as follows: Grind the raw materials with a planetary mill to a fineness of 74μm square hole sieve with a sieve residue of <5%. Weigh the weight percentages as follows: 47.65% limestone, 28.59% high silicon limestone 1, 6.73% aluminum ash, 8.58% fly ash, 8.46% gypsum; the ions added according to the oxide content in the clinker are ZnO: 1.0%, CaF2: 1.0%. Mix the weighed raw materials for 12 hours to prepare raw material powder; add 8% water by weight to the raw material powder, mix evenly, press it into a 60mm*60mm*5mm square raw material cake with a press, and dry it in a 100℃ blast dryer for 8 hours. After drying, heat the raw material cake to 900℃ at a heating rate of 10℃ / min and keep it for 30 minutes, then heat it to 1300℃ and keep it for 30 minutes. Then it is quickly taken out and air-cooled to room temperature to obtain alite-belite-calcium sulphoaluminate clinker. The product XRD pattern is as follows: Figure 1 The quantitative results of clinker minerals are shown in Table 3. The clinker is mixed with 8% by mass of dihydrate gypsum to obtain a mixed powder, which is ground by a disc vibration mill to a particle size of about 74 μm and a sieve residue of ≤5%, to obtain alite-belite-calcium sulfoaluminate cement. Example 5

[0036] The preparation method of alite-belite-calcium sulfoaluminate cement in Example 5 is as follows: Grind the raw materials with a planetary mill to a fineness of 74μm square hole sieve with a sieve residue of <5%. Weigh the weight percentages as follows: 37.06% limestone, 41.83% high silicon limestone 1, 9.06% aluminum ash, 2.65% fly ash, 9.40% gypsum; the ions added according to the oxide content in the clinker are ZnO: 1.0%, CaF2: 1.0%. Mix the weighed raw materials for 12 hours to prepare raw material powder; add 8% water by weight to the raw material powder, mix evenly, press it into a 60mm*60mm*5mm square raw material cake with a press, and dry it in a 100℃ blast dryer for 8 hours. After drying, heat the raw material cake to 900℃ at a heating rate of 10℃ / min and keep it for 30 minutes, then heat it to 1300℃ and keep it for 30 minutes. Then it is quickly taken out and air-cooled to room temperature to obtain alite-belite-calcium sulphoaluminate clinker. The product XRD pattern is as follows: Figure 1 The quantitative results of clinker minerals are shown in Table 3. The clinker is mixed with 8% by mass of dihydrate gypsum to obtain a mixed powder, which is ground by a disc vibration mill to a particle size of about 74 μm and a sieve residue of ≤5%, to obtain alite-belite-calcium sulfoaluminate cement.

[0037] Table 3 Clinker mineral composition (wt / %)

[0038] The cement of each of the above-mentioned embodiments was made into slurry samples and tested for 3-day, 7-day and 28-day strength. The preparation steps are as follows: Take an appropriate amount of alite-belite-calcium sulfoaluminate cement, use a water-cement ratio of 0.4, and stir in a mixer for 3-4 minutes; pour the stirred cement slurry into a 20mm*20mm*20mm standard cement slurry mold, and vibrate it on a cement mortar vibrating table for 60s; scrape off the excess cement slurry on the mold surface, and place it in a standard cement concrete curing box for 24 hours; then demold the specimen, and then place the cement slurry test block in a 95% RH, 20°C standard curing box and cure it to 3d, 7d, and 28d ages respectively. The test results are as follows: Figure 2 shown.

[0039] Depend on Figure 2 It can be seen that the alite-belite-calcium sulfoaluminate cement clinker fired at low temperature by mixing high-silicon low-grade limestone and aluminum solid waste has strong early performance, and the strength continues to develop in the middle and late stages without shrinkage. Compared with Example 1 in which inferior raw materials are not used, the cement strength of other embodiments using inferior raw materials is slightly reduced, but the overall impact is small.

[0040] The present invention replaces low-grade limestone and aluminum solid waste to prepare low-calcium and high-performance alite-belite-calcium sulfoaluminate cement clinker, which saves raw materials for cement production, reduces production costs, and can solve the problems of difficult utilization and high recycling costs of bulk solid waste, and can also promote the development of the cement industry in a low-carbon direction.

[0041] The present invention provides an idea and method for preparing alite-belite-calcium sulfoaluminate cement clinker and method using high-silicon low-grade limestone and aluminum solid waste. There are many methods and ways to implement the technical solution. The above-mentioned specific implementation of the present invention does not constitute a limitation on the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. An alite-belite-calcium sulfoaluminate cement clinker prepared from high-silicon low-grade limestone and aluminum solid waste, characterized in that: The mineral phase composition of the clinker is calculated by mass percentage, including C3S: 30~50%, C2S: 30~50%, C4A3$: 10~30%, C4AF: 0~5%, CaSO4: 0~5%, and metal ion oxides; The oxide contents, in percentage by mass, include CaO: 50-65%, SiO2: 15-25%, Al2O3: 8-15%, Fe2O3: 0-3%, and SO3: 3-8%; the raw materials of the alite-belite-calcium sulfoaluminate cement clinker include high-silicon low-grade limestone, aluminum solid waste, gypsum and mineralizer.

2. The alite-belite-calcium sulfoaluminate cement clinker prepared from high-silicon low-grade limestone and aluminum solid waste according to claim 1, characterized in that: The metal ion oxide includes any one of MnO2, ZnO, and CuO or a combination of two or more thereof.

3. The alite-belite-calcium sulfoaluminate cement clinker prepared from high-silicon low-grade limestone and aluminum solid waste according to claim 1, characterized in that: The high-silicon low-grade limestone has a CaO content of 39-46 wt % and a SiO2 content of 18-29 wt %.

4. The alite-belite-calcium sulfoaluminate cement clinker prepared from high-silicon low-grade limestone and aluminum solid waste according to claim 1, characterized in that: The aluminum solid waste is aluminum ash or fly ash, or a mixture of the two in any proportion; the Al2O3 content in the aluminum solid waste is greater than 60 wt%.

5. The alite-belite-calcium sulfoaluminate cement clinker prepared from high-silicon low-grade limestone and aluminum solid waste according to claim 1, characterized in that: Calculated by mass percentage, the calcium raw material content in the raw meal is 70~83%, the aluminum raw material content is 5~15%, and the sulfur raw material content is 5~10%.

6. The alite-belite-calcium sulfoaluminate cement clinker prepared from high-silicon low-grade limestone and aluminum solid waste according to claim 1, characterized in that: The mineralizer is CaF2.

7. The method for preparing alite-belite-calcium sulfoaluminate cement clinker according to claim 1, characterized in that: The steps include: (1) Grinding a calcium raw material, an aluminum raw material and a sulfur raw material, and then fully mixing them, and then adding metal ion oxides and a mineralizer and mixing them evenly to obtain a raw meal; (2) Calcine the raw material of step (1) at 1250°C to 1350°C for 15 to 30 minutes, then take it out and cool it quickly to obtain the product.

8. The method for preparing alite-belite-calcium sulphoaluminate cement clinker according to claim 7, characterized in that: In step (1), the metal ion oxide is added in an amount of 0.5-2% of the mass of cement clinker; and the mineralizer is added in an amount of 1-2% of the mass of cement clinker.

9. The method for preparing alite-belite-calcium sulphoaluminate cement clinker according to claim 7, characterized in that: In step (1), all raw materials are ground and mixed thoroughly, and the mixed powder particle size is 74µm mesh sieve residue ≤5 wt %.

10. The method for preparing alite-belite-calcium sulfoaluminate cement clinker according to claim 7, characterized in that: In step (2), the heating rate of calcination is 5-10°C / min, and after calcination, the mixture is rapidly cooled to room temperature by air cooling.